Pengaruh Konsentrasi Inhibitor Ekstrak Daun Sirsak terhadap Laju Korosi Baja Karbon - Ryana Dwi Shafira; Arriza Mulyana; Medyan Riza (Jurnal Inovasi Ramah Lingkungan, 2022)
Corrosion is a degradation of metal because of its reaction with the environment. The use of inhibitors is one of the most effective ways to prevent corrosion. Corrosion inhibitors are substances which when added to a metal can slow down the corrosion rate. Soursop leaf is one of the plants which contains tannin. Utilization of soursop leaf in the industrial world is still rarely done so that it is possible to use the soursop leaf as a natural inhibitor in the corrosion reaction of steel. This research uses socletation extraction method to extract tannins on soursop leaf and use mass reduction method to know the rate of corrosion. The independent variables of this research are the ratio of soursop leaf powder and ethanol-water solvent: 1:99; 2:98; 3:97; 4:96; 5:95 (w/w), long immersion: 5; 10; and 15 days, and corrosive media and inhibitor ratio: 1:0; 1:1; 1:2; and 1:3 (v/v). The result showed that in immersion without inhibitors, the sample has the highest weight loss or the highest corrosion rate.  The result for the immersion with the addition of inhibitor indicates that the soursop leaf extract can reduce the corrosion rate. Inhibitors that has the most effective result to reduce the corrosion rate is the concentration of 5% and contact time of 15 days with the lowest value of 0.0098 mg / cm2 perday at the ratio of corrosive media: inhibitor 1:3. Soursop leaf extract provides the greatest corrosion rate inhibitor with a value of 93.33 obtained at a concentration of 5%, the ratio of corrosive media:inhibitor 1:3 and contact time of 15 days.